Antithrombin III in Full-Term and Pre-Term Newborn Infants : Three Cases of Neonatal Diagnosis of AT III Congenital Defect - De Stefano, V; Leone, G; De Carolis, M P; Ferrelli, R; De Carolis, S; Pagano, L; Tortorolo, G; Bizzi, B (Thrombosis and Haemostasis, 1987)
Antithrombin III (AT III) plasma levels were investigated in 18 full term neonates and 14 healthy preterm neonates. A control group of 20 healthy adults was also studied. AT III was measured as antigen concentration (Ag) and antithrombin or anti-factor Xa heparin cofactor (H. C.) activities. Crossed immunoelectrophoresis on heparin-agarose (H-CIE) was carried out on plasma samples; moreover the distribution of isoantithrombins was investigated on whole plasma by a technique of crossed immunoelectrofocusing (CIEF). AT III plasma levels in full term infants were significantly lower as compared to the adult values. The preterm newborns group showed a further significant decrease in AT III levels as compared to the full term neonates. In all infants AT III H-CIE runs displayed a single fast moving anodal peak, so that a normal binding to heparin was demonstrated. The CIEF AT III plasma pattern of the adults as well as of all neonates displayed three major peaks at pH range 5.2-4.9, a small amount of AT III at pH 4.9-4.8 and a minor peak at pH 4.8-4.6, so that it was concluded that the isoantithrombins plasma distribution in neonatal age is identical to that of the adult subjects. Four neonates whose mothers were affected by AT III congenital defect were also investigated: diagnosis of congenital deficiency was established in three cases.
Keywords: Antithrombin III; Newborn AT III levels; AT III congenital defect